2022
DOI: 10.3390/ijerph19063626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diagnostic Delay on Survival Rates for Patients with Colorectal Cancer

Abstract: Colorectal cancer affects men and women alike. Sometimes, due to clinical-pathological factors, the absence of symptoms or the failure to conduct screening tests, its diagnosis may be delayed. However, it has not been conclusively shown that such a delay, especially when attributable to the health system, affects survival. The aim of the present study is to evaluate the overall survival rate of patients with a delayed diagnosis of colorectal cancer. This observational, prospective, multicenter study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Low and middle‐income countries experience a higher burden and low 5 years survival rates among colorectal cancer patients compared with developed countries 10 . Previous studies demonstrated that late diagnosis had the worst survival in colorectal cancer patients 20,21 . Inadequate health coverage may restrict access to optimal diagnostic and therapeutic care, which can negatively affect the desired treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low and middle‐income countries experience a higher burden and low 5 years survival rates among colorectal cancer patients compared with developed countries 10 . Previous studies demonstrated that late diagnosis had the worst survival in colorectal cancer patients 20,21 . Inadequate health coverage may restrict access to optimal diagnostic and therapeutic care, which can negatively affect the desired treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Previous studies demonstrated that late diagnosis had the worst survival in colorectal cancer patients. 20 , 21 Inadequate health coverage may restrict access to optimal diagnostic and therapeutic care, which can negatively affect the desired treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the performance of screening tests and the evolution of new cases vary between regions, making it difficult to extrapolate with confidence all the results found in the literature 28 . It has been observed that in rural and marginalized areas belonging to low‐ and middle‐income countries, where there is a considerable volume of population (mainly due to farming and livestock activities or armed conflict situations), most of whom are elderly, there are inequities in education and screening interventions, which would explain difficulties in access to and compliance with therapeutic regimens and strict follow‐up, which increases mortality 29,30 . Taking into account, the aggressive behavior of colorectal cancer observed in the population studied, it can be inferred, for example, that the population of the rural area with lower education and greater economic hardship, are late in presenting gastrointestinal symptoms suggestive of the presence of cancer, which would explain the frequency of late stages of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 28 It has been observed that in rural and marginalized areas belonging to low‐ and middle‐income countries, where there is a considerable volume of population (mainly due to farming and livestock activities or armed conflict situations), most of whom are elderly, there are inequities in education and screening interventions, which would explain difficulties in access to and compliance with therapeutic regimens and strict follow‐up, which increases mortality. 29 , 30 Taking into account, the aggressive behavior of colorectal cancer observed in the population studied, it can be inferred, for example, that the population of the rural area with lower education and greater economic hardship, are late in presenting gastrointestinal symptoms suggestive of the presence of cancer, which would explain the frequency of late stages of diagnosis. Therefore, these findings could support that in similar populations, which also have a high prevalence of comorbidities and are also exposed to tropical diseases, personalized strategies should be designed to promote screening and early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The American Cancer Society reports that the colorectal cancer 5-year survival rate varies greatly depending on the stage at diagnosis. Patients with localized tumors (stages I–II) have a 5-year survival rate of nearly 90%, while those with stage III have a survival rate of nearly 72% compared to a much lower rate for those with stage IV and distant metastases, which is around 14% ( Padilla-Ruiz et al, 2022 ; Siegel et al, 2023b ). This discrepancy underlines the crucial significance of early detection using methods that can overcome difficulties presented by conventional diagnostic approaches and enhance the general prognosis for those affected by these illnesses.…”
Section: Introductionmentioning
confidence: 99%